Doctors and the patients’ claims. Analysis of judicial practice - Iwona Wrześniewska-Wal (Wiedza Medyczna, 2020)
Patient rights have an increasingly significant impact on the conditions of therapy and on daily clinical practice. The fact that law might affect the doctor’s approach is confirmed in particular by the case law illustrating the claiming attitude of patients. The purpose of this study is to discuss selected verdicts of medical courts which show that it is not always the diagnosis and treatment that the patients complain about. It is important to review those issues in order to include them in the teaching programs for undergraduate and postgraduate students of medicine